RPI and RPL clasp masticatory load distribution in lower free end denture case with photoelastic methods - Sutanto, Dahlia; Mahmud, Muslich; Rahajoeningsih, Poedji (Universitas Padjadjaran, 2007)
The extent and direction of movement of removable partial dentures during function are influenced by the nature of supporting structures and the design of the prosthesis since forces are transmitted to abutment teeth by rest, guide planes, and direct retainers during functional movements. Because of the lack of tooth support distally, the denture base will have tissueward underfunction proportionate to the quality (displaceability) of the supporting soft tissue, the accuracy of the denture base, and the total occlusal load applied. The movement of the base under function determines the occlusal efficiency of the partial denture and the degree to which the abutment teeth are subjected to torque and tipping stresses.The purpose of this study is to know the functional load exerts with RPI and RPL direct retainer in bilateral distal extension. This study is a laboratory experiment employing samples of 5 frames using RPI and 5 frames using RPL direct retainer design. Testing was conducted by Vishay Teaching Polariscope type 080. The result was noted and analyzed statistically using ANOVA.The result of this study indicates that F calculation value for frame with RPI and RPL direct retainer design is 5,35 and 6,11 Mpa; F calculation for the occlusal load distribution on first premolar and edentulous area is 276,90 Mpa and 171,53 Mpa; F calculation for occlusal load distribution on first premolar and edentulous area employing RPI and RPL direct retainer design is 9,17 and 11,96 Mpa. This statistical calculation shows that there is a significant difference between RPI and RPL direct retainer design, the occlusal load concentrated at edentulous area either RPI or RPL direct retainer, and the occlusal load distribution between the first premolar and edentulous area are more uniform on RPI direct retainer design.